Teachersâ€™ Perception of School-Based Assessment in Nigerian Secondary Schools - Adediwura, Alaba Adeyemi (Richtmann Publishing, 2012)
The study investigated the perceived effect of SBA on Nigerian secondary school teachers, with the specific aim ofdetermining the preparedness of the teachers to conduct SBA as well as the perceived effect of the SBA on their teachingpractices and studentsâ€™ learning. The population for the study consist of secondary school teachers in the six South-WesternState of Nigeria. From each of the six states, six secondary schools were purposively selected based on owner ship of theschools. A total number of 36 secondary schools were involved in the study. From each of the schools 15 teachers wererandomly selected to take part in the study. Thus the study sample size was 540 teachers. An adapted questionnaire was usedto collect the study data. The adapted questionnaire was named â€œNigerian Teachersâ€™ Perception of School-Based AssessmentQuestionnaireâ€. This questionnaire was divided into four sections of A, B, C and D. Sections B, C, and D of the instrumentrespectively have a test-retest reliability of (r = 0.72, 0.77 & 0.73 Ï = < .05) over a period of two weeks and Cronbach coefficientalpha (0.79, 0.70 and 0.71). The result indicated that more than half of the sampled teachers were not adequately prepare toconduct SBA. However, teachers from Federal Government Colleges were better prepared. It was also discovered that morethan fifty percent of the teachers have a negative perception of the effect of SBA on their teaching practices and on studentsâ€™learning. The study therefore suggests effective monitoring of educational policy implementation and timely in-service trainingfor all teachers irrespective of school owner.